Counterfactual thought. [article]. - Bryne, Ruth M.J
People spontaneously create counterfactual alternatives to reality when they think "if only" or "what if" and imagine how the past could have been different. The mind computes counterfactuals for many reasons. Counterfactuals explain the past and prepare for the future, they implicate various relations including causal ones, and they affect intentions and decisions. They modulate emotions such as regret and relief, and they support moral judgements such as blame. The loss of the ability to imagine alternatives as a result of injuries to the prefrontal cortex is devastating. The basic cognitive processes that compute counterfactuals mutate aspects of the mental representation of reality to create an imagined alternative, and they compare alternative representations. The ability to create counterfactuals develops throughout childhood and contributes to reasoning about other people's beliefs, including their false beliefs. Knowledge affects the plausibility of a counterfactual through the semantic and pragmatic modulation of the mental representation of alternative possibilities. . -- (from the authors)